FORMULATION DEVELOPMENT OF IMMEDIATE RELEASE PELLETS OF TADALAFIL: SOLIDIFICATION APPROACH FOR NANOSUSPENSION: SOLIDIFICATION APPROACH FOR NANOSUSPENSION - UBGADE, SHOBHA; KILOR, VAISHALI; BAHEKAR, VIDYA; ITTADWAR, ABHAY (International Journal of Applied Pharmaceutics, 2019)
Objective: Nanosuspension is known to enhance the saturation solubility and dissolution velocity of poorly soluble drugs owing to the increased surface area of nanosized particles. Stability of these solubility enhancing systems can be improved by converting them into solidified forms. To simultaneously achieve enhanced dissolution and improved stability, an attempt has been made to increase the dissolution rate of poorly soluble drug tadalafil by formulating immediate release pellets of its nanosuspension. Methods: Tadalafil nanosuspensions were prepared using high shear homogenization technique and hydroxypropyl methylcellulose (HPMC) E 15, sodium dodecyl sulphate (SDS) as stabilizers. Prepared nanosuspensions were subjected to the characterization of particle size distribution, zeta potential, drug loading and saturation solubility. Optimized nanosuspension was solidified by preparing immediate release pellets: for improved stability, where tadalafil nanosuspension was used as a binder. Pellets were prepared by extrusion-spheronization technique using κ-carrageenan as a pelletizing aid. Results: Prepared immediate release pellets disintegrated within 03 min. In vitro dissolution studies showed 85% drug release within 45 min in pH 1.2 buffer from immediate release pellets containing tadalafil nanosuspension. Conclusion: It can be concluded that formulation of nanosuspension of poorly soluble drug and its use as a binder for the preparation of immediate release pellets markedly improved the dissolution rate.